2017
DOI: 10.1161/circulationaha.116.022069
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Cardioprotective Effects at the ADAMTS7 Locus as a Result of Gene-Smoking Interactions

Abstract: Background Common diseases such as coronary heart disease (CHD) are complex in etiology. The interaction of genetic susceptibility with lifestyle factors may play a prominent role. However, gene-environment interactions for CHD have been difficult to identify. Here, we investigate interaction of smoking behavior, a potent lifestyle factor, with genotypes that have been shown to associate with CHD risk. Methods We analyzed data on 60,919 CHD cases and 80,243 controls from 29 studies for gene-smoking interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 37 publications
3
28
1
1
Order By: Relevance
“…Finally, a recent study reported that of the 45 loci known to associate with CAD risk, a variant at ADAMTS7 rs7178051, which is in modest linkage disequilibrium with rs3825807 (LD=0.52), exhibited an important gene‐smoking interaction in 61 000 cases with coronary heart disease and 80 000 controls . The protective effect of ADAMTS7 genetic variation on CAD risk was found to be lower in persons who smoked than in nonsmokers, while exposure of human coronary cell lines to cigarette smoke led to induction of ADAMTS7 activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a recent study reported that of the 45 loci known to associate with CAD risk, a variant at ADAMTS7 rs7178051, which is in modest linkage disequilibrium with rs3825807 (LD=0.52), exhibited an important gene‐smoking interaction in 61 000 cases with coronary heart disease and 80 000 controls . The protective effect of ADAMTS7 genetic variation on CAD risk was found to be lower in persons who smoked than in nonsmokers, while exposure of human coronary cell lines to cigarette smoke led to induction of ADAMTS7 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Genome‐wide association studies have revealed a robust association between genetic variation in the ADAMTS7 (a disintegrin and metalloprotease with thrombospondin motif 7) gene on chromosome 15q25 and clinical phenotypes of coronary artery disease (CAD) . One of the lead single nucleotide polymorphisms (SNPs), rs3825807, is an adenine (A) to guanine (G) substitution located in exon 4 of the ADAMTS7 gene, with the G allele conferring a reduced risk of CAD, and is found to be in linkage disequilibrium with other SNPs such as rs1994016 and rs7178051 commonly studied at the ADAMTS7 loci. This nonsynonymous SNP leads to an amino acid change in the prodomain of the ADAMTS7 protein, a metalloproteinase that plays a role in proteolysis and degradation of extracellular matrix in connective tissues .…”
mentioning
confidence: 99%
“…Big data offers special contributions to precision public health in enabling a wider view of health variables through linking disparate or novel data ( 44 , 153 , 154 ) and enabling large study populations with volumes of multiomic data to identify “molecular cohorts” ( 155 ).…”
Section: Contributions Of Big Datamentioning
confidence: 99%
“…The interaction of genes and environment have produced the interesting observation that Allelic variations at rs7178051 that are associated with reduced ADAMTS7 expression confers CAD protection which is stronger in never-smokers than in cigarette smokers [36] . Enhanced vascular ADAMTS7 expression may lead to the loss of protection from CAD which occurs in cigarette smokers leading to the suggestion that inhibition of ADAMTS7 maybe especial helpful for individuals who smoke cigarettes [36] .…”
Section: Coronary Artery Atherosclerosismentioning
confidence: 99%